Synthesis and Study the Mesomorphic Behaviour of New N- acetyl and Their Diazetine: Mono and Twin - Ghali, Thaer S.; Tomma, Jumbad H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
Synthesis ,characterization of new mono and twin compounds containing heterocyclic four member ring as, 1,3- diazetine by four steps. The first step; includes preparation of 2- amino thiazole derivatives [I]a-c via ring closure reaction between acetophenone derivatives with thiourea in I2, while the second step includes condensation reaction between 2-amino thaizole derivatives[I]a-c and p-methoxy benzaldehyde to produce Schiff bases[II]a-c. The third step includes neculophilic attach from imine group toacetyl chloride to give N- acetyl cross bonding[III]a-c.Finally ; the fourth step is completed by the reaction of N- acetyl derivatives with sodium azide (NaN3) to yield new 1,3-diazetines. The synthesized compounds were characterized byNMR and IR spectroscopy .The study of liquid crystalline behaviour was carried out using optical polarising microscopy (OPM) and some of them by differential scanning calorimetry (DSC) . All compounds were synthesized which showed liquid crystalline properties on heating.